2006
DOI: 10.1161/circulationaha.106.638627
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Study Comparing Same-Day Home Discharge and Abciximab Bolus Only to Overnight Hospitalization and Abciximab Bolus and Infusion After Transradial Coronary Stent Implantation

Abstract: for the Early Discharge After Transradial Stenting of Coronary Arteries (EASY) Study InvestigatorsBackground-Systematic use of coronary stents and optimized platelet aggregation inhibition has greatly improved the short-term results of percutaneous coronary interventions. Transradial percutaneous coronary interventions have been associated with a low risk of bleeding complications. It is unknown whether moderate-and high-risk patients can be discharged safely the same day after uncomplicated transradial percut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
211
0
14

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 328 publications
(235 citation statements)
references
References 46 publications
10
211
0
14
Order By: Relevance
“…These results are in agreement with previous studies of PCI using the transradial (9,12) or transfemoral approach (8,10,12). In our population of clinically stable patients referred for PCI, most of the patients were eligible for ambulatory management.…”
Section: Safety and Feasibility Of Outpatient Transradial Pcisupporting
confidence: 92%
See 3 more Smart Citations
“…These results are in agreement with previous studies of PCI using the transradial (9,12) or transfemoral approach (8,10,12). In our population of clinically stable patients referred for PCI, most of the patients were eligible for ambulatory management.…”
Section: Safety and Feasibility Of Outpatient Transradial Pcisupporting
confidence: 92%
“…These changes have called into question the need for an overnight hospital stay after PCI in patients with stable angina. Although several large-scale prospective studies have assessed the feasibility and safety of same-day home discharge after PCI (8)(9)(10)12), additional data collected under the conditions of everyday practice are required before ambulatory PCI can be used on a routine basis.…”
Section: Safety and Feasibility Of Outpatient Transradial Pcimentioning
confidence: 99%
See 2 more Smart Citations
“…It was also the period when young investigators set up a large clinical program in invasive cardiology. In a randomized trial (68), they showed the feasibility and safety of same-day discharge after percutaneous coronary intervention. The investigators are presently leading a multicentre trial on intervention aimed at the regression/stabilization of atherosclerotic plaques.…”
Section: The 2000s: a Period Of Expansionmentioning
confidence: 99%